Link layer modeling of bio-inspired communication in nanonetworks - Arifler, Do?u (My University, 2011)
Bio-inspired packet communication over a link between two nanogateways is considered. In the envisioned nanonetwork architecture, bacteria are employed as transporters of information packets between gateways and therefore, the link layer model must take into account the behavior of these transporters. With the unique features of this mode of communication integrated into a simulation software, single-hop delay and throughput performance measures are analyzed. The effects on performance of traffic generation intensity, source-destination separation distance, propagation time variability, packet lifetime, and the number of bacteria that can be processed concurrently at the nanogateway are presented. The primary contribution of this study is an assessment of the effects of congestion in nanonetworks through consideration of competition among bacteria for conjugation at a nanogateway. © 2011 Elsevier Ltd.
Keywords: Bacteria-based communication; Discrete-event simulation; Nanonetworks; Performance evaluation